Growing the Performance of SMEs with Islamic Financial Literacy and Spirituality - Supriyanto, Achmad Sani; Diana, Ilfi Nur; Suprayitno, Eko; Ekowati, Vivin Maharani; Mardiana (Universitas Brawijaya, Indonesia, 2025)
SMEs can achieve sustainable competitive advantage and superior profitability if they possess valuable resources and capabilities. Financial literacy is one such intangible resource that helps equip individuals with the knowledge and information necessary to manage budgets and make strategic investment decisions. Financial literacy is a person's knowledge of improving the quality of decision-making and financial management to achieve welfare. This study aims to determine the effect of Islamic financial literacy of SMEs actors on the growth of SMEs’ performance. Testing the Islamic spirituality as moderating the effect of Islamic financial literacy on the spirituality of SMEs’ performance. The method used in this study is quantitative research with an explanatory approach to prove the truth of the hypothesis. The population in this study consisted of small and medium-sized enterprises (SMEs) actors in Malang City, East Java, with the criteria of being Muslim. The sample used in the study was obtained using the Slovin formula with a precision of 5%, so a sample of 200 respondents was obtained. The data collection technique used a questionnaire distributed to 200 respondents and analyzed using Partial Least Squares (PLS). The findings reveal that Islamic financial literacy directly and significantly affects SMEs’ performance. Islamic spirituality can moderate the effect of Islamic financial literacy on SMEs’ performance. Based on the results of this study, it is hoped that SMEs’ actors will know what factors need to be considered to improve their business performance. Future studies should include other variables and expand the topic of discussion regarding the sustainability of SMEs’ performance related to innovation, Islamic business ethics, and spirituality in the workplace.